Struktur Komunitas Fitoplankton pada Budidaya Ikan Koi (Cyprinus Rubrosfuscus) dalam Sistem Vertiqua Menggunakan Biofikal Filter Atas - M Yasa; Ujang Dindin; Neneng Nurbaeti (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2024)
Vertiqua biofical top filter is a cultivation technique with a recirculation system that utilizes limited land. Vertiqua is a solution for cultivation. When cultivating koi fish in vertiqua, the feed capacity increases and there is a high nutrient load so that the waters are easily polluted, therefore the presence of an upper biophysical filter can reduce pollution. This is important to study, especially the structure of the phytoplankton community because it is one of the biological indicators of ponds in koi fish cultivation. This research was carried out for 6 weeks in Sindangpalay Ciberem Sukabumi. The research was carried out by taking phytoplankton in the vertiqua at intervals of once every 2 weeks. The data analysis in this research is abundance, diversity, uniformity and dominance. During the research results obtained were abundance 636-673, diversity 2.6, uniformity 0.9, and dominance 0.01. The water quality studied was ammonia, nitrate, nitrite, phosphate, pH, DO, turbidity and temperature. These waters are stable and healthy, which is a positive indicator to support fish farming activities. The water quality in Vertiqua is classified as good and the ecosystem is balanced, these waters are ideal for supporting the productivity and health of farmed fish.